Answer:
[tex]x={-\frac{3\sqrt{2}}{2}, \frac{3}{4}, \frac{3\sqrt{2}}{2}}[/tex]
Step-by-step explanation:
In order to find the zeros of a function, we must first set the equation equal to zero, so we get:
[tex]8x^{3}-6x^{2}-36x+27=0[/tex]
so we can now solve this by factoring. We can factor this equation by grouping. We start by grouping the equation in pairs of terms, so we get:
[tex](8x^{3}-6x^{2})+(-36x+27)=0[/tex]
and factor each group, so we get:
[tex]2x^{2}(4x-3)-9(4x-3)=0[/tex]
and now factor again, so we get:
[tex](2x^{2}-9)(4x-3)=0[/tex]
and now we set each of the factors equal to zero to find the zeros:
[tex]2x^{2}-9=0[/tex]
[tex]2x^{2}=9[/tex]
we divide both sides into 2 to get:
[tex]x^{2}=\frac{9}{2}[/tex]
and take the square root to both sides to get:
[tex]x=\pm\sqrt{\frac{9}{2}}[/tex]
which yields:
[tex]x=\pm\frac{3}{\sqrt{2}}[/tex]
We rationalize so we get:
[tex]x=\pm\frac{3\sqrt{2}}{2}[/tex]
this means that we have two zeros here:
[tex]x=\frac{3\sqrt{2}}{2}[/tex] and [tex]x=-\frac{3\sqrt{2}}{2}[/tex]
so we take the other factor and set it equal to zero.
4x-3=0
and solve for x
4x=3
[tex]x=\frac{3}{4}[/tex]
and that will be our third zero.